Lieky s mechanizmom pulzného uvoľňovania - Sabadková, Dana; Franc, Aleš; Muselík, Jan; Neumann, David; Vetchý, David (Chemické listy, 2015)
This review is focused on the basic principles of the delivery systems with a pulsatile release pattern. Such systems are designed according to the circadian rhythm of the body. Time-controlled, stimuli-induced and externally regulated pulsatile drug delivery systems are recognized. The drug release of time-controlled systems occurs after a predefined time lag. Stimuli-induced systems release the drug as a reaction to changeable conditions in the body (pH, glucose level). The drug release of externally regulated systems is controlled via external stimulus (magnetism, ultrasound). Pulsatile drug delivery systems rank among modern dosage forms which provide many therapeutic benefits.
Keywords: Pulse Therapy, Drug; pulzní dávkování léků; lékové transportní systémy; farmaceutická technologie; Drug Delivery Systems; cirkadiánní rytmus; Delayed-Action Preparations; Technology, Pharmaceutical; léky s prodlouženým účinkem; Circadian Rhythm